Systemic Inflammatory Cytokine Analysis to Monitor Biomaterial Augmented Tissue Healing. Issue 12 (December 2015) - Bryan, Nicholas; Ashwin, Helen; Smart, Neil; Weyhe, Dirk; Wohlert, Stephen; Bayon, Yves; Hunt, John A.
Purpose: Hernias can be repaired by reinforcement of damaged fascia using biomaterials to provide stabilisation. Repair materials are usually porous, through which cells infiltrate, proliferate and secrete ECM. Their efficacy relies on good tissue integration and resolution of host defence mechanisms. Therefore, understanding the dynamics by which biomaterials interact with tissue will provide knowledge to advance prosthesis design. Furthermore, determining host response in real time would provide significant advantage both clinically and scientifically over the current terminal process of histology. Methods: 3 materials comprising synthetic and composite (synthetic materials hybridised with a resorbable biologic component) meshes were implanted into a rat full-thickness abdominal wall excision model. Their efficacy was evaluated using histopathology whilst also monitoring systemic concentrations of cytokines associated with inflammation and wound healing to predict material outcome over 12 weeks. Results: The noncomposite material (polyester) and Material B (polypropylene mesh with oligocaprone film and polydioxanone glue) stimulated the largest degree of adhesion from the 3 materials tested, although after 28 days adhesions were stronger to Material B. Histologically, all 3 materials integrated well with abdominal musculature and infiltrated completely with cells. Conclusions: Analysis of systemic inflammation biomarkers confirmed inflammation elicited by surgeries and meshes irrespective of their composition. However, at an early postoperative endpoint (i.e., 1 week), some biomarkers, namely, IL-18 and RANTES, appeared to discriminate the noncomposite mesh from the composite materials, although in this study all materials successfully repaired the defects without recurrence or external indicators of postoperative chronic pain.